T Cell Motility as Modulator of Interactions with Dendritic Cells - Stein, Jens V. (Frontiers in Immunology, 2015)
It is well established that the balance of costimulatory and inhibitory signals during interactions with dendritic cells (DCs) determines T cell transition from a naïve to an activated or tolerant/anergic status. While many of these molecular interactions are well reproduced in reductionist in vitro assays, the highly dynamic motility of naïve T cells in lymphoid tissue acts as an additional lever to fine-tune their activation threshold. T cell detachment from DCs providing suboptimal stimulation allows them to search for DCs with higher levels of stimulatory signals, while storing a transient memory of short encounters. In turn, adhesion of weakly reactive T cells to DCs presenting pMHC with low affinity is prevented by lipid mediators. Finally, controlled recruitment of CD8+ T cells to cognate DC – CD4+ T cell clusters shapes memory T cell formation and the quality of the immune response. Dynamic physiological lymphocyte motility therefore constitutes a mechanism to mitigate low avidity T cell activation and to improve the search for “optimal” DCs, while contributing to peripheral tolerance induction in the absence of inflammation.